Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1179/1937525514y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of augered cast in place pile capacity using static loading tests

Abstract: Instrumented static loading tests present an effective tool for appropriate engineering of piled foundations. Whether instrumented or not, considerable effort can be expended to determine the interpreted failure load developed during the loading test, and the determination of an appropriate capacity is often subject to regulatory review and discussion, which may be complicated by the large number of interpretation methods available and the large range in interpreted capacities that could result. This paper foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In comparison, the results indicated that Brinch Hansen 80% method is the most accurate method among extrapolation methods in determining the failure load. The term ultimate failure of the pile is inappropriate to refer to continuous settlement under constant load, according to Stuedlein [11]. Therefore, the summary of the study emphasized the adoption of interpretation methods in determining the failure load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the results indicated that Brinch Hansen 80% method is the most accurate method among extrapolation methods in determining the failure load. The term ultimate failure of the pile is inappropriate to refer to continuous settlement under constant load, according to Stuedlein [11]. Therefore, the summary of the study emphasized the adoption of interpretation methods in determining the failure load.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the 15 methods mentioned above were applied to each pile. Finally, the final bearing capacity was obtained with the specific settlement of each pile, where both load and settlement are done according to ASTM D 1143 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Stuedlein et al [1] discuss the challenges associated with the determination of "capacity" or "failure load" from static load tests. The authors argue that the most significant source of differences in the interpreted capacity from static load tests stems from the number of methods available for the interpretation of the static load test data.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the measured resistances from the L 1 -L 2 method are generally higher than the results from the slope tangent method. It has been recognized by Kulhawy and Chen (2005), NeSmith and Siegel (2009), and Stuedlein et al (2014) that the slope tangent method underestimates the ultimate pile axial Fig. R3.…”
mentioning
confidence: 99%